Robert McCauley and Ernest Thomas Lawson, Philosophical Foundations of the Cognitive Science of Religion. (14th February 2020) - Van Eyghen, Hans
Abstract : Robert McCauley and Ernest Thomas Lawson, Philosophical Foundations of the Cognitive Science of Religion